Public Expenditures on Social Programs and Household Consumption in China - Baldacci, Emanuele; Callegari, Giovanni; Coady, David; Ding, Ding. (Washington, D.C. : International Monetary Fund, 2010)
This paper shows that increasing government social expenditures can make a substantive contribution to increasing household consumption in China. The paper first undertakes an empirical study of the relationship between the savings rate and social expenditures for a panel of OECD countries and provides illustrative estimates of their implications for China. It then applies a generational accounting framework to Chinese household income survey data. This analysis suggests that a sustained 1 percent of GDP increase in public expenditures, distributed equally across education, health, and pensions, would result in a permanent increase the household consumption ratio of 1u percentage points of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet